On Consonances of the Visible and the Audible - Gedgaudas, Edmundas (Problemos, 1983)
For almost five decades Liudas Truikys, a Lithuanian artist (b. 1904), has devoted himself to searching a most exact expression of these interactions that by his creative imagination are born at the encounter of music and visual forms during an opera performance. Gradually giving up illustrations to the subject, he is striving, by means of plastic forms, for a greater disclosing of the powers creating the form of a musical performance and penetrating the universality of its purport. Interpreting and supplementing to opera scores, in consonances of the visible and audible, the artist reveals a new metaphorical character which extends the sense capacity in classical operas.